Modelling Innovation Paths of European Firms using Fuzzy Balanced Scorecard - Hájek, Petr; Stejskal, Jan; Kotková Stříteská, Michaela; Prokop, Viktor (International Society of Science and Applied Technologies, 2019)
Modelling innovation paths is considered a difficult task because innovation processes are complex, uncertain and highly dimensional. As traditional regression models fail to address these issues, here we propose a novel approach for the modelling. The approach integrates Balanced Scorecard, a method used for strategic performance assessment, and fuzzy set qualitative comparative analysis. In addition to key performance indicators, strategic goals are taken into consideration in the modelling. We provide empirical evidence for the effectiveness of the approach on a large dataset of European firms. We show that several innovation pathways can be identified for these firms, depending on their strategic goals. These results may be of relevance for the decision making of innovative firms and other actors of innovation system.
Modelování způsobů inovační tvorby v Evropských firmách pomocí Fuzzy Balanced Scorecard
Keywords: Modelling; Innovation; Paths; European; Firms; using; Fuzzy; Balanced; Scorecard; Modelování; způsobů; inovační; tvorby; Evropských; firmách; pomocí; Fuzzy; Balanced; Scorecard